A survey of East Palaearctic Gnaphosidae (Araneae). 3. On new and poorly known Gnaphosa Latreille, 1804 - Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2014)
Two new species, Gnaphosa koponeni sp. n. (♂♀, Tuva, Russia) and G. tunevae sp. n. (♀, Mongolia) are described. New figures and distribution data are provided for G. gracilior Kulczyński, 1901, G. kansuensis Schenkel, 1963, G. mandschurica Schenkel, 1963, G. sticta Kulczyński, 1908, G. stoliczkai O. Pickard-Cambridge, 1885 and G. wiehlei Schenkel, 1963. Additional morphological evidence is provided that G. similis Kulczyński, 1926 is not a synonym of G. muscorum (L. Koch, 1866). Gnaphosa stoliczkai is reported from Mongolia for the first time. The synonymy of Gnaphosa potanini Simon, 1895 with G. silvicola Kamura, 1988 is discussed and is likely to be incorrect.